2021
DOI: 10.1371/journal.pone.0247117
|View full text |Cite
|
Sign up to set email alerts
|

High density optical neuroimaging predicts surgeons’s subjective experience and skill levels

Abstract: Measuring cognitive load is important for surgical education and patient safety. Traditional approaches of measuring cognitive load of surgeons utilise behavioural metrics to measure performance and surveys and questionnaires to collect reports of subjective experience. These have disadvantages such as sporadic data, occasionally intrusive methodologies, subjective or misleading self-reporting. In addition, traditional approaches use subjective metrics that cannot distinguish between skill levels. Functional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 50 publications
(21 reference statements)
0
36
0
Order By: Relevance
“…Notably, the use of questionable ‘experts’ was not limited to the James et al (2011) study. Keles et al (2021) performed expertise level classification using machine learning techniques. They compared PFC activity in novice medical students compared to attending surgeons in laparoscopic peg transfer and string threading tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the use of questionable ‘experts’ was not limited to the James et al (2011) study. Keles et al (2021) performed expertise level classification using machine learning techniques. They compared PFC activity in novice medical students compared to attending surgeons in laparoscopic peg transfer and string threading tasks.…”
Section: Resultsmentioning
confidence: 99%
“…A total mental workload score was obtained from the sum of the criteria scores. To analyze the fNIRS data, source-detector pair readings (with a separation of 3.35 cm) at two distinct wavelengths are rst converted into hemoglobin concentration changes via the modi ed Beer-Lambert law, and the average of the task episode are calculated (3). In this paper the standard deviation of the oxyhemoglobin concentration changes over an episode is denoted HbO and represents the extent of local cortical activation of a subject during the corresponding experimental episode.…”
Section: Discussionmentioning
confidence: 99%
“…After the video session the 15 min training was repeated by each subject for gamers and non-gamers. Further details of the procedure were provided in a recent study where we reported an analysis of the brain activity of surgeons and a subset of the student participants without regard to game playing experience (3). All participants lled out a questionnaire detailing their video game experience including the frequency, duration and category.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…While mainly the lateral portion of BA 6 of the frontal cortex showed activation for tasks i-iii, both the lateral and the medial portions of BA 6, including the premotor cortex and the supplementary motor area (SMA), showed activation in the most complex bimanually coordinated task v. In order to investigate these neural correlates (brain aspect) of laparoscopic surgery training, functional near infrared spectroscopy (fNIRS) can provide a better temporal resolution and ease of administration when compared to fMRI; however, at a lower spatial resolution and signal-to-noise ratio (SNR) [2]. Many prior works [3][4][5][6][7] have assessed surgery training using fNIRS mainly to compare skill levels; however, we could not find prior works on portable neuroimaging to compare surgery training in physical versus virtual simulators. This is crucial since surgical training field has seen a rapid emergence of new virtual training technologies which are gradually replacing physical training simulators with virtual training simulators.…”
Section: Introductionmentioning
confidence: 99%